Balloon Guide Catheter is Not Superior to Conventional Guide Catheter when Stent Retriever and Contact Aspiration are Combined for Stroke Treatment. Issue 1 (27th July 2020) - Bourcier, Romain; Marnat, Gaultier; Labreuche, Julien; Desal, Hubert; Maria, Federico Di; Consoli, Arturo; Eugène, François; Gory, Benjamin; Dargazanli, Cyril; Blanc, Raphaël; Lapergue, Bertrand
Abstract: BACKGROUND: The effectiveness of balloon guide catheter (BGC) use has not been prospectively studied and its added value for improving reperfusion in acute ischemic stroke (AIS) treatment has only been reported in studies in which no contact aspiration was combined with the stent retriever (CA + SR). OBJECTIVE: To compare the reperfusion results and clinical outcomes with and without BGC use when a combined CA + SR strategy is employed in first line to treat AIS. METHODS: From January 2016 to April 2019, data from the ETIS registry (Endovascular Treatment in Ischemic Stroke) were reviewed. We included patients having undergone endovascular treatment with a combined CA + SR strategy and use or not of a BGC according to the operator's discretion. We compared BGC and nonBGC populations with matching and inverse probability of treatment weighting propensity scores. Primary outcome was the final near-complete/complete revascularization (mTICI2c/3) rate. Secondary outcomes included clinical outcomes and safety considerations. RESULTS: Among 607 included patients, BGC was used in 32.9% (n = 200), and 190 matched pairs could be found. We found no significant difference in final mTICI2c/3 between patients with and without BGC (60.1% in BGC group compared to 62.7% in nonBGC group (matched RR, 0.92; 95%CI, 0.80 to 1.14)), first-pass mTICI2c/3 (35.1% vs 37.3%, matched RR, 0.94; 95%CI, 0.68 to 1.30), clinical outcome (matched RR of 1.12 (95%CI, 0.85 to 1.47) for favorable outcome. CONCLUSION: The reperfusion and clinical results with and without BGC use are not significantly different when combined CA + SR are used as a first-line strategy for large vessel occlusion in the setting of AIS. Graphical Abstract: